Viajar no Feminino – As palavras das Imagens: Viagem de Egéria à Terra Santa, séc. IV - Limão, Filomena (2015)
Egéria was a 4th century A.D. nun who undertook a long journey from her homeland, the roman province of Gallaecia, to the Near East. Her itinerary, which described the segment between Mount Sinai and Constantinople, revealed the enthusiasm which graced her original decision to embark on the journey, and the determination with which she faced every stage. She kept a Diary throughout her journey. Probably, it constitutes one of the first known Travel Diaries. Her reports describe her observations and the splendor of the Christian cult sites. Her text is affectionately dedicated to her fellow nuns that remained in the West of the Empire, keeping their uniting bond strong. Our study aims to search all references to visited sites in Egéria’s text, as the information contained therein serves as a precious descriptor of their locations, spatial organization and environment. Egéria visits unique, historical sites, which will influence her writing style. She is, in fact, a pilgrim to a recently created historical site, The Holy Land. Egéria lived during a fundamental historical and artistic Framework, that of the architectural forms of expression of the First Christianity. Her words can be translated into images, as a partitions script, a visualization of lights and ambiences, and a testimonial of places that no longer exist. We hope to see, in Egéria’s written work, the images she observed, for her words are images. We expect a complementary approach among the research methods given by Archeology, composed by Architecture and explained by the sensible text from Egéria’s journey - a religious and artistic journey written from a powerful feminine point of view.